Institutional Transformation of the Al-Birr College as a form of Regeneration Scholars in University of Muhammadiyah - Ali Bakri, Muhammad; Arsyad, Azhar; Khalifah Mustami, Muhammad; Yaumi, Muhammad (Advances in Social Sciences Research Journal, 2019)
This study aims to describe and analyze institutional transformation of the Al-Birr college as a form of Regeneration Scholars in University of Muhammadiyah Makassar, which includes aspects of (1) institutional management, (2) institutional transformation process and (3) output of Al-Birr college institutional transformation in University of Muhammadiyah Makassar. This type of research is descriptive qualitative research through phenomenological approaches. Data collection techniques using open interviews, observation and documentation studies. Determination of data sources was done purposively with data analysis techniques namely data reduction, data presentation, and drawing conclusions and verification to analyze data. The results showed that (1) the implementation institutional management of Al-Birr college in aspects of leadership management, educators, student affairs, curriculum, learning systems, infrastructure and financial systems, had fundamentally and substantially achieved organizational goals with effective and efficient. This institutional management system produces a unique management design in managing educational and dakwah (Da‘wah literally means “issuing a summons” or “making an invitation”, Tabligh literally means ‘to convey’. Contextually, it refers to conveying the message of Islam) institutions as educational models oriented to philanthropy or charity project. College institutional management is generally carried out centrally and autonomously under the supervision of the Asia Muslim Charity Foundation in Jakarta. (2) the process of college institutional transformation refers to the background of the establishment, vision, mission, goals, structure, and organizational culture that results in the strategic program to produce Ulama in University of Muhammadiyah Makassar. Strategic program of Al-Birr college are training and sending da'I (Ulama) in remote areas, Al-quran memorizing school, syariah and dakwah programs and integration program for Ulama Tarjih Muhammadiyah (PUTM). (3) the output of institutional transformation has resulted many graduates and da'is who have roles in providing guidance and effective community service.